The Association of Aromatic Amino Acids with Incident Hip Fracture, aBMD, and Body Composition from the Cardiovascular Health Study. - Le, Brian; Bůzková, Petra; Robbins, John A; Fink, Howard A; Raiford, Mattie; Isales, Carlos M; Shikany, James M; Coughlin, Steven S; Carbone, Laura D (Calcif Tissue Int, 2019)
In 5187 persons from the Cardiovascular Health Study, there was no significant association of dietary intakes of aromatic amino acids (AAA) with areal BMD of the hip or body composition. However, those who had the lowest dietary intakes of AAA were at increased risk for incident hip fractures. Prior studies of the association of protein intake with osteoporosis are conflicting and have not directly examined the relationship of aromatic amino acids (AAA) with fractures, areal bone mineral density (aBMD), and body composition. We sought to determine the relationship of dietary intakes of AAA with osteoporosis parameters in elderly men and women. 5187 men and women aged ≥ 65 years from the Cardiovascular Health Study (CHS) with dietary intakes of AAA (tryptophan, phenylalanine, tyrosine) estimated by food frequency questionnaire (FFQ) were included. We examined the relationship between a one-time estimate of daily dietary AAA intake with risk of incident hip fractures over a median of 13.2 years of fracture follow-up. A subset (n = 1336) who had dual energy X-ray absorptiometry (DXA) performed were included in a cross-sectional analysis of the association of dietary AAA intake with aBMD of the total hip and measurements of body composition. In multivariable models adjusted for demographic and clinical variables, medication use, and diet, higher dietary AAA intake was not significantly associated with incident hip fractures. All hazard ratios (HR) were less than one (tryptophan, HR 0.14, 95% CI 0.01 to 1.89; phenylalanine, HR 0.60, 95% CI 0.23 to 1.55; tyrosine, HR 0.59, 95% CI 0.27 to 1.32), but confidence intervals were wide and included no difference. However, in post hoc analyses, the lowest quartile of intake for each AAA was associated with an increased risk for hip fracture compared to higher quartiles (p ≤ 0.047 for all). Dietary AAA intakes were not significantly associated with total hip aBMD or any measurements of body composition. Overall, there was no significant association of dietary AAA intake with hip fractures, aBMD of the hip, or body composition. However, there may be a subset of elderly individuals with low dietary intakes of AAA who are at increased for hip fractures.

Association of Dietary Niacin Intake With Incident Hip Fracture, BMD, and Body Composition: The Cardiovascular Health Study. - Carbone, Laura D; Bůzková, Petra; Fink, Howard A; Raiford, Mattie; Le, Brian; Isales, Carlos M; Shikany, James M; Coughlin, Steven S; Robbins, John A (J Bone Miner Res, 2019)
Interest in niacin has increased in the setting of reports suggesting that niacin plays a role in diseases of aging. No study to date has examined the association of dietary niacin intake with multiple skeletal health parameters including bone mineral density (BMD), hip fractures, and body composition, and none have included both African American and white men and women. Participants included 5187 men and women ≥65 years from the Cardiovascular Health Study (CHS). Mean daily dietary niacin intake was 32.6 mg, with quartiles 1 through 4 defined as 3.6 to 21.8 mg/day, 21.9 to 30.2 mg/day, 30.3 to 40.9 mg/day, and 41.0 to 102.4 mg/day, respectively. Risk of incident hip fracture per 10 mg increment of daily dietary niacin intake was estimated using proportional hazards models. During a median follow-up of 13 years, 725 participants had an incident hip fracture. In models adjusted for demographic and clinical characteristics and diet, dietary niacin intake was significantly associated with an increased risk of hip fractures (hazard ratio [HR] 1.12; 95% CI, 1.01 to 1.24) with spline models suggesting a U-shaped association. In post hoc analyses, both the lowest (HR 1.31; 95% CI, 1.04 to 1.66) and highest (HR 1.53; 95% CI, 1.20 to 1.95) quartiles of niacin intake were associated with an increased risk of incident hip fracture versus quartiles 2 and 3. There was a trend for a significant inverse association of dietary niacin intake with hip BMD (p = 0.06), but no significant association with total body BMD or any body composition measures. In this cohort of elderly, community-dwelling African American and white men and women, both high and low dietary niacin intakes were associated with a significantly increased risk of subsequent hip fracture, suggesting a possible U-shaped association. By comparison, dietary niacin may have an inverse linear association with hip BMD. © 2018 American Society for Bone and Mineral Research.

Gene-educational attainment interactions in a multi-ancestry genome-wide meta-analysis identify novel blood pressure loci. - de Las Fuentes, Lisa; Sung, Yun Ju; Noordam, Raymond; Winkler, Thomas; Feitosa, Mary F; Schwander, Karen; Bentley, Amy R; Brown, Michael R; Guo, Xiuqing; Manning, Alisa; Chasman, Daniel I; Aschard, Hugues; et al. (Mol Psychiatry, 2020)
Educational attainment is widely used as a surrogate for socioeconomic status (SES). Low SES is a risk factor for hypertension and high blood pressure (BP). To identify novel BP loci, we performed multi-ancestry meta-analyses accounting for gene-educational attainment interactions using two variables, "Some College" (yes/no) and "Graduated College" (yes/no). Interactions were evaluated using both a 1 degree of freedom (DF) interaction term and a 2DF joint test of genetic and interaction effects. Analyses were performed for systolic BP, diastolic BP, mean arterial pressure, and pulse pressure. We pursued genome-wide interrogation in Stage 1 studies (N = 117 438) and follow-up on promising variants in Stage 2 studies (N = 293 787) in five ancestry groups. Through combined meta-analyses of Stages 1 and 2, we identified 84 known and 18 novel BP loci at genome-wide significance level (P < 5 × 10). Two novel loci were identified based on the 1DF test of interaction with educational attainment, while the remaining 16 loci were identified through the 2DF joint test of genetic and interaction effects. Ten novel loci were identified in individuals of African ancestry. Several novel loci show strong biological plausibility since they involve physiologic systems implicated in BP regulation. They include genes involved in the central nervous system-adrenal signaling axis (ZDHHC17, CADPS, PIK3C2G), vascular structure and function (GNB3, CDON), and renal function (HAS2 and HAS2-AS1, SLIT3). Collectively, these findings suggest a role of educational attainment or SES in further dissection of the genetic architecture of BP.

Multi-Ancestry Genome-wide Association Study Accounting for Gene-Psychosocial Factor Interactions Identifies Novel Loci for Blood Pressure Traits. - Sun, Daokun; Richard, Melissa; Musani, Solomon K; Sung, Yun Ju; Winkler, Thomas W; Schwander, Karen; Chai, Jin Fang; Guo, Xiuqing; Kilpeläinen, Tuomas O; Vojinovic, Dina; Aschard, Hugues; Bartz, Traci M; et al. (HGG Adv, 2021)
Psychological and social factors are known to influence blood pressure (BP) and risk of hypertension and associated cardiovascular diseases. To identify novel BP loci, we carried out genome-wide association meta-analyses of systolic, diastolic, pulse, and mean arterial BP taking into account the interaction effects of genetic variants with three psychosocial factors: depressive symptoms, anxiety symptoms, and social support. Analyses were performed using a two-stage design in a sample of up to 128,894 adults from 5 ancestry groups. In the combined meta-analyses of Stages 1 and 2, we identified 59 loci (p value <5e-8), including nine novel BP loci. The novel associations were observed mostly with pulse pressure, with fewer observed with mean arterial pressure. Five novel loci were identified in African ancestry, and all but one showed patterns of interaction with at least one psychosocial factor. Functional annotation of the novel loci supports a major role for genes implicated in the immune response (), synaptic function and neurotransmission (), as well as genes previously implicated in neuropsychiatric or stress-related disorders (). These findings underscore the importance of considering psychological and social factors in gene discovery for BP, especially in non-European populations.

Multi-ancestry genome-wide gene-sleep interactions identify novel loci for blood pressure. - Wang, Heming; Noordam, Raymond; Cade, Brian E; Schwander, Karen; Winkler, Thomas W; Lee, Jiwon; Sung, Yun Ju; Bentley, Amy R; Manning, Alisa K; Aschard, Hugues; Kilpeläinen, Tuomas O; Ilkov, Marjan; et al. (Mol Psychiatry, 2021)
Long and short sleep duration are associated with elevated blood pressure (BP), possibly through effects on molecular pathways that influence neuroendocrine and vascular systems. To gain new insights into the genetic basis of sleep-related BP variation, we performed genome-wide gene by short or long sleep duration interaction analyses on four BP traits (systolic BP, diastolic BP, mean arterial pressure, and pulse pressure) across five ancestry groups in two stages using 2 degree of freedom (df) joint test followed by 1df test of interaction effects. Primary multi-ancestry analysis in 62,969 individuals in stage 1 identified three novel gene by sleep interactions that were replicated in an additional 59,296 individuals in stage 2 (stage 1 + 2 P < 5 × 10), including rs7955964 (FIGNL2/ANKRD33) that increases BP among long sleepers, and rs73493041 (SNORA26/C9orf170) and rs10406644 (KCTD15/LSM14A) that increase BP among short sleepers (P < 5 × 10). Secondary ancestry-specific analysis identified another novel gene by long sleep interaction at rs111887471 (TRPC3/KIAA1109) in individuals of African ancestry (P = 2 × 10). Combined stage 1 and 2 analyses additionally identified significant gene by long sleep interactions at 10 loci including MKLN1 and RGL3/ELAVL3 previously associated with BP, and significant gene by short sleep interactions at 10 loci including C2orf43 previously associated with BP (P < 10). 2df test also identified novel loci for BP after modeling sleep that has known functions in sleep-wake regulation, nervous and cardiometabolic systems. This study indicates that sleep and primary mechanisms regulating BP may interact to elevate BP level, suggesting novel insights into sleep-related BP regulation.